The influence of estuary eutrophication on the benthic diatom community: a molecular approach. Issue 2 (3rd April 2021) - Nunes, M; Lemley, DA; Matcher, GF; Adams, JB
Abstract : The occurrence of harmful algal blooms (HABs) is increasing in frequency and intensity in South African estuaries because of eutrophication. This study used DNA metabarcoding to identify the benthic diatom community structure in the eutrophic Sundays Estuary. The recurrent HAB phytoplankton species Heterosigma akashiwo was recorded at bloom concentrations (∼100 µg Chl a l −1 ) in the brackish, vertically stratified middle reaches of the estuary. In contrast, microphytobenthos biomass increased towards the upper reaches in response to elevated availability of total oxidised nitrogen (NOx ) and increased sediment stability. A total of 76 diatom species were identified using the molecular technique. Seven known nutrient-tolerant diatom species indicate a preference for either ammonium or NOx enrichment. Benthic diatom community diversity ( H ′ < 1) and evenness ( J ′ < 0.25) were low in the brackish middle reaches of the estuary, where the HABs decreased available light. Heterosigma akashiwo has been found in previous studies to suppress the growth of co-occurring taxa. Future research efforts should focus on verifying this relationship over seasonal timescales given the dominance of H. akashiwo in spring/summer. As the persistently nutrient-enriched state and stable flow conditions of the Sundays Estuary is the key driver of change, management efforts should be geared towards re-establishing the estuary's natural flow variations and to measures that can mitigate nutrient pollution.